Effect of Herbal Therapy on Reducing Dysmenorrhea Pain Scale in Adolescents - Antina, Rila Rindi; Soliha, Soliha; Wulandari, Novita (Journal of Midwifery, 2024)
Menstruation is an event that naturally (normally) occurs in women who are entering reproductive age. Menstruation occurs because the uterus sheds its endometrial lining periodically. One of the menstrual problems that often arises is dysmenorrhea. This study aims to analyze differences in dysmenorrhea pain scales with herbal therapy of papaya leaf decoction and red ginger decoction. The design used in this study is an experimental quesy through the Pretest-Posttest None equivalent Control Group approach. Samples were taken using non-probability sampling with accidental sampling techniques. The results of the research data were carried out by a bivariate test with a T-test with Î±: 0.05. Based on the results of the study, the difference after being given papaya leaf decoction and red ginger stew had a mean of 1.66 for papaya leaf decoction and a mean of 1.22 for red ginger stew. The results of the T-Test statistical test showed a result of 0.875 which is greater than Î±, so it can be concluded that there is no difference between the administration of papaya leaf decoction therapy and red ginger stew. Based on the results of these studies, a decoction of papaya leaves and ginger can be used as an alternative therapy to reduce menstrual pain